INNOVATIVE APPROACH TO WASTEWATER TREATMENT - Azimov, Sh.; Mirzaeva, D.; Egamberdiev, E.; Turabdajanov, S. (Educational Research in Universal Sciences, 2024)
The potential of algae in the purification of chrome wastewater was studied and its results were presented. In addition, the culture of Azolla caroliniana, which is tolerant to high levels of chromium (Cr), was obtained, based on the chromium-adapted cultures of Azolla, the wastewater treatment processes with high chromium content were analyzed. Sorption processes of chromium in the dry mass of Azolla were carried out and the research results were analyzed.